“INFLUENCIA DE LOS RECURSOS DIDÁCTICOS UTILIZADOS POR LAS MAESTRAS EN EL PROCESO ENSEÑANZA APRENDIZAJE DE LA MATEMÁTICA DE LAS NIÑAS DE TERCER AÑO DE EDUCACIÓN BÁSICA DEL CENTRO EDUCATIVO “MAGDALENA DÁVALOS” DE LA PARROQUIA VELOZ, CANTÓN RIOBAMBA, PROVINCIA DE CHIMBORAZO, DURANTE EL AÑO LECTIVO 2012-2013” - Chávez Erazo, Julia Verónica (2014)
The research was based on the theories of the constructivist paradigm and significant learning, who determine the pupil as the main protagonist in the construction of their own knowledge. The process of teaching mathematics is aim to the development of essential skills such as reasoning, logical thinking, critical thinking, argumentation founded and the resolution of problems. This will serve to make the students capable of solving everyday problems, at the same time strengthens the creativity by means of the connection between theory and practice. The development of logical mathematical intelligence is achieved by linking several factors such as the teacher's methodology, innovative teaching resources, the motivation in the classroom, the affectivity among others. The results that outstand from this research show that the use of teaching resources help to improve learning and academic performance in the mathematics area; But it has been shown that in the classroom is not fully complete with the didactic and methodological recommendations that is set in the updating and strengthening curriculum of the Basic General Education of third year. It was also prove that there is a problem regard to the development of the real meaningful learning, this is due to that teachers should use with greater frequency range the teaching resources such as those found in the school context. Since the first years of study it is essential that in the teaching-learning process of mathematics linked the previous knowledge with the new ones, using correctly the types of teaching resources so the knowledge will be durable. Finally, it is proposed the development of the Alternative didactic Guide, and work to correct this problem, with the aim of promoting the use of teaching resources of the school context.